Does colectomy predispose to small intestinal bacterial (SIBO) and fungal overgrowth (SIFO)?. Issue 4 (April 2018) - Rao, Satish S. C.; Tan, George; Abdulla, Hamza; Yu, Siegfried; Larion, Sebastian; Leelasinjaroen, Pornchai
Abstract : Objectives: : After subtotal colectomy, 40% of patients report chronic gastrointestinal symptoms and poor quality of life. Its etiology is unknown. We determined whether small intestinal bacterial overgrowth (SIBO) or small intestinal fungal overgrowth (SIFO) cause gastrointestinal symptoms after colectomy. Methods: : Consecutive patients with unexplained abdominal pain, gas, bloating and diarrhea (>1 year), and without colectomy (controls), and with colectomy were evaluated with symptom questionnaires, glucose breath test (GBT) and/or duodenal aspiration/culture. Baseline symptoms, prevalence of SIBO/SIFO, and response to treatment were compared between groups. Results: : Fifty patients with colectomy and 50 controls were evaluated. A significantly higher ( p = 0.005) proportion of patients with colectomy, 31/50 (62%) had SIBO compared to controls 16/50 (32%). Patients with colectomy had significantly higher ( p = 0.017) prevalence of mixed SIBO/SIFO 12/50 (24%) compared to controls 4/50 (8%). SIFO prevalence was higher in colectomy but not significant ( p = 0.08). There was higher prevalence of aerobic organisms together with decreased anaerobic and mixed organisms in the colectomy group compared to controls ( p = 0.008). Patients with colectomy reported significantly greater severity of diarrhea ( p = 0.029), vomiting ( p < 0.001), and abdominal pain ( p = 0.05) compared to controls, at baseline. After antibiotics, 74% of patients with SIBO/SIFO in the colectomy and 69% in the control group improved ( p = 0.69). Conclusion: : Patients with colectomy demonstrate significantly higher prevalence of SIBO/SIFO and greater severity of gastrointestinal symptoms. Colectomy is a risk factor for SIBO/SIFO.